Communicative-Pragmatic Assessment Is Sensitive and Time-Effective in Measuring the Outcome of Aphasia Therapy - Benjamin Stahl; Benjamin Stahl; Benjamin Stahl; Benjamin Stahl; Bettina Mohr; Felix R. Dreyer; Guglielmo Lucchese; Friedemann Pulvermüller; Friedemann Pulvermüller (Frontiers in Human Neuroscience, 2017)
A range of methods in clinical research aim to assess treatment-induced progress in aphasia therapy. Here, we used a crossover randomized controlled design to compare the suitability of utterance-centered and dialogue-sensitive outcome measures in speech-language testing. Fourteen individuals with post-stroke chronic non-fluent aphasia each received two types of intensive training in counterbalanced order: conventional confrontation naming, and communicative-pragmatic speech-language therapy (Intensive Language-Action Therapy, an expanded version of Constraint-Induced Aphasia Therapy). Motivated by linguistic-pragmatic theory and neuroscience data, our dependent variables included a newly created diagnostic instrument, the Action Communication Test (ACT). This diagnostic instrument requires patients to produce target words in two conditions: (i) utterance-centered object naming, and (ii) communicative-pragmatic social interaction based on verbal requests. In addition, we administered a standardized aphasia test battery, the Aachen Aphasia Test (AAT). Composite scores on the ACT and the AAT revealed similar patterns of changes in language performance over time, irrespective of the treatment applied. Changes in language performance were relatively consistent with the AAT results also when considering both ACT subscales separately from each other. However, only the ACT subscale evaluating verbal requests proved to be successful in distinguishing between different types of training in our patient sample. Critically, testing duration was substantially shorter for the entire ACT (10–20 min) than for the AAT (60–90 min). Taken together, the current findings suggest that communicative-pragmatic methods in speech-language testing provide a sensitive and time-effective measure to determine the outcome of aphasia therapy.